PENGEMBANGAN MEDIA ONLINE EDMODO PADA PEMBELAJARAN FISIKA MATERI MOMENTUM DAN IMPULS UNTUK SISWA KELAS X SEKOLAH MENENGAH ATAS - Budiman, Arif; Sudrajat, Hendar; Fakhruddin Z, Fakhruddin Z (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This is aimed to design Edmodo Media as learning media Physics focusing on momentum and impuls. This research was conducted since March until Juny 2018. It used R and D research methodology and it used ADDIE as learning media planning model. The instrument which is technique which is used in collecting the data was by validating the media planning by validator. Data analysis technique which is used was conducted for two times by doing suggestion by the validator. The first validity result shows 4,00 which is categorized high for material aspect, 4.10 which is categorized high for visual aspect, and 4.18 which is categorized high for learning design aspect. The second validation was conducted after revision. The result of the second validation was 4.30 which is categorized very high for material aspect, 4.27 which is categorized very high for visual aspect, and 4.40 which is categorized vey high for learning design aspect. Finally, the edmodo online learning media has been developed for impuls and momentum material. This learning media has very high validity which make it suitable used as learning media for impuls and momentum material.Key Words : Reseach and Development, ADDIE, Edmodo online media